An update of safety of clinically used atypical antipsychotics. Issue 10 (2nd October 2016) - Orsolini, L.; Tomasetti, C.; Valchera, A.; Vecchiotti, R.; Matarazzo, I.; Vellante, F.; Iasevoli, F.; Buonaguro, E. F.; Fornaro, M.; Fiengo, A. L. C.; Martinotti, G.; Mazza, M.; et al.
ABSTRACT: Introduction: The atypical antipsychotic (APs) drugs have become the most widely used agents to treat a variety of psychoses because of their superiority with regard to safety and tolerability profile compared to conventional/'typical' APs. Areas covered : We aimed at providing a synthesis of most current evidence about the safety and tolerability profile of the most clinically used atypical APs so far marketed. Qualitative synthesis followed an electronic search made inquiring of the following databases: MEDLINE, Embase, PsycINFO and the Cochrane Library from inception until January 2016, combining free terms and MESH headings for the topics of psychiatric disorders and all atypical APs as following: ((safety OR adverse events OR side effects) AND (aripiprazole OR asenapine OR quetiapine OR olanzapine OR risperidone OR paliperidone OR ziprasidone OR lurasidone OR clozapine OR amisulpride OR iloperidone)). Expert opinion: A critical issue in the treatment with atypical APs is represented by their metabolic side effect profile (e.g. weight gain, lipid and glycaemic imbalance, risk of diabetes mellitus and diabetic ketoacidosis) which may limit their use in particular clinical samples. Electrolyte imbalance, ECG abnormalities and cardiovascular adverse effects may recommend a careful baseline and periodic assessments.